Measuring Capacity for Resilience among Coastal Counties of the US Northern Gulf of Mexico Region - Reams, Margaret A. (Am J Clim Change, 2012)
Many have voiced concern about the long-term survival of coastal communities in the face of increasingly intense storms and sea level rise. In this study we select indicators of key theoretical concepts from the social-ecological resilience literature, aggregate those indicators into a resilience-capacity index, and calculate an index score for each of the 52 coastal counties of Louisiana, Texas, Mississippi, Alabama and Florida. Building upon Cutter’s Social Vulnerability Index work [1], we use Factor Analysis to combine 43 variables measuring demographics, social capital, economic resources, local government actions, and environmental conditions within the counties. Then, we map the counties’ scores to show the spatial distribution of resilience capacities. The counties identified as having the highest resilience capacities include the suburban areas near New Orleans, Louisiana and Tampa, Florida, and the growing beach-tourist communities of Alabama and central Florida. Also, we examine whether those counties more active in oil and gas development and production, part of the region’s “energy coast”, have greater capacity for resilience than other counties in the region. Correlation analyses between the resilience-capacity index scores and two measures of oil and gas industry activity (total employment and number of business establishments within five industry categories) yielded no statistically significant associations. By aggregating a range of important contextual variables into a single index, the study demonstrates a useful approach for the more systematic examination and comparison of exposure, vulnerability and capacity for resilience among coastal communities.